Effects of lng Mutations on LngA Expression, Processing, and CS21 Assembly in Enterotoxigenic Escherichia coli E9034A - Saldaña-Ahuactzi, Zeus; Rodea, Gerardo E.; Cruz-Córdova, Ariadnna; Rodríguez-Ramírez, Viridiana; Espinosa-Mazariego, Karina; González-Montalvo, Martín A.; Ochoa, Sara A.; González-Pedrajo, Bertha; Eslava-Campos, Carlos A.; López-Villegas, Edgar O.; Hernández-Castro, Rigoberto; Arellano-Galindo, José; et al. (Frontiers in Microbiology, 2016)
Enterotoxigenic Escherichia coli (ETEC) is a major cause of morbidity in children under 5 years of age in low- and middle-income countries and a leading cause of traveler's diarrhea worldwide. The ability of ETEC to colonize the intestinal epithelium is mediated by fimbrial adhesins, such as CS21 (Longus). This adhesin is a type IVb pilus involved in adherence to intestinal cells in vitro and bacterial self-aggregation. Fourteen open reading frames have been proposed to be involved in CS21 assembly, hitherto only the lngA and lngB genes, coding for the major (LngA) and minor (LngB) structural subunit, have been characterized. In this study, we investigated the role of the LngA, LngB, LngC, LngD, LngH, and LngP proteins in the assembly of CS21 in ETEC strain E9034A. The deletion of the lngA, lngB, lngC, lngD, lngH, or lngP genes, abolished CS21 assembly in ETEC strain E9034A and adherence to HT-29 cells was reduced 90%, compared to wild-type strain. Subcellular localization prediction of CS21 proteins was similar to other well-known type IV pili homologues. We showed that LngP is the prepilin peptidase of LngA, and that ETEC strain E9034A has another peptidase capable of processing LngA, although with less efficiency. Additionally, we present immuno-electron microscopy imagens to show that the LngB protein could be localized at the tip of CS21, and probably helps to control CS21 length. In conclusion, our results demonstrate that the LngA, LngB, LngC, LngD, LngH, and LngP proteins are essential for CS21 assembly, as well as for bacterial aggregation and adherence to HT-29 cells.